Oxymatrine inhibits aldosterone-induced rat cardiac fibroblast proliferation and differentiation by attenuating smad-2, -3 and-4 expression: an in vitro study. Issue 1 (December 2016) - Fu, Lingyun; Xu, Yini; Tu, Ling; Huang, Haifeng; Zhang, Yanyan; Chen, Yan; Tao, Ling; Shen, Xiangchun
Abstract Background We previously demonstrated oxymatrine, an alkaloid from the Chinese medicine radixSophorae flavescentis, ameliorates hemodynamic disturbances and cardiac fibrosis; however, the underlying mechanisms are unclear. Here, we investigated the effect and mechanism of action of oxymatrine on aldosterone-induced cardiac fibroblast to myofibroblast differentiation in vitro. Methods Cardiac fibroblasts were isolated purified from neonatal Sprague Dawley rats. The optimal concentration of aldosterone to stimulate cardiac fibroblast proliferation was determined using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Cardiac fibroblasts were pretreated with 7.57 × 10−4 mol/L or 3.78 × 10−4 mol/L oxymatrine or without oxymatrine for 2 h, and then coincubated with 1 × 10−8 mol/L aldosterone for 48 h. The MTT assay and Masson staining were used to detect the cardiac fibroblast proliferation and myofibroblast differentiation. The secretion of type I and III collagen was measured by commercial ELISA kits, and the hydroxyproline content was determined by the colorimetric assay. Western blotting assayed the Smad-2, Smad-3, and Smad-4 protein expression in cardiac fibroblasts. Results The present results confirmed that aldosterone induced cardiac fibroblast to myofibroblast proliferation and differentiation. The MTT assay and Masson staining indicated oxymatrine significantly inhibited aldosterone-induced cardiac fibroblast proliferation and myofibroblast differentiation. Oxymatrine significantly inhibited aldosterone-induced secretion of type I and III collagen, as indicated by commercial ELISA kits, and aldosterone-induced increase in hydroxyproline content, as indicated by a colorimetric assay. Western blotting revealed oxymatrine attenuated aldosterone-induced Smad-2, Smad-3, and Smad-4 expression in cardiac fibroblasts. Conclusion Oxymatrine can inhibit cardiac fibroblast proliferation and differentiation into myofibroblasts via a mechanism linked to attenuation of the Smad signaling pathway.